Improving Understanding of Bank Reconciliation Through Education and Training at Ricci I Jakarta - Chelsya Chelsya (Yayasan Pendidikan Bukhari Dwi Muslim, 2026)
Purpose: This Community Service Activity (PKM) aims to enhance students’ understanding of the concepts and practices of bank reconciliation as part of a company’s internal controls. The program was implemented due to students’ limited understanding of how bank reconciliation is applied in the business world. Method: The activity was held in person at Ricci I High School in West Jakarta on April 17, 2026, and lasted two hours, involving 28 eleventh-grade students. The methods used included planning, instruction through the presentation of materials, training and guidance through practice exercises, evaluation using Quizizz-based pre- and post-tests, and a participant satisfaction survey. Results and Discussion: Before the training, most students did not understand bank reconciliation. After the intervention, understanding increased, as evidenced by an average post-test score of 87. Participants also showed great enthusiasm throughout the activity. The program’s outputs included journal articles, intellectual property, and educational posters. Implications: This program helps improve students' accounting literacy and supports the SDGs related to quality education. Further training with more hands-on practice is needed.